2020
DOI: 10.1038/s41419-020-2584-z
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LL22NC03-N14H11.1 promoted hepatocellular carcinoma progression through activating MAPK pathway to induce mitochondrial fission

Abstract: Involvement of long non-coding RNAs (lncRNAs) in hepatocarcinogenesis has been largely documented. Mitochondrial dynamics is identified to impact survival and metastasis in tumors including hepatocellular carcinoma (HCC), but the underlying mechanism remains poorly understood. This study planned to explore the regulation of lncRNA LL22NC03-N14H11.1 on HCC progression and mitochondrial fission. Dysregulated lncRNAs in HCC are identified through circlncRNAnet and GEPIA bioinformatics tools. Biological function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Another study showed the role of a long non-coding RNA (lncRNA)—L22NC03-N14H11.1—in the tumor progression of hepatocellular carcinoma ( Yi et al, 2020 ). L22NC03-N14H11.1 had increased expression in patients diagnosed with stage III/IV cancer compared to those diagnosed with stage I/II.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed the role of a long non-coding RNA (lncRNA)—L22NC03-N14H11.1—in the tumor progression of hepatocellular carcinoma ( Yi et al, 2020 ). L22NC03-N14H11.1 had increased expression in patients diagnosed with stage III/IV cancer compared to those diagnosed with stage I/II.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, LINC00152 can be used as a novel potential LIHC prognostic marker. As for RP11‐620J15.3, it was the former transcript of hepatocarcinogenesis (GIHCG), and its overexpression was related to poor prognosis and immune infiltration of hepatocellular carcinoma (HCC) 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…As for RP11‐620J15.3, it was the former transcript of hepatocarcinogenesis (GIHCG), and its overexpression was related to poor prognosis and immune infiltration of hepatocellular carcinoma (HCC). 36 , 37 . However, the molecular regulatory mechanism of RP11‐620J15.3 on the prognosis of LIHC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, downregulation of BANCR via shRNA-mediated knockdown inactivated the MAPK/ERK signaling in HCC cells, leading to the suppression of cellular proliferation and migration [ 65 ]. Other lncRNAs, such as IGF2AS, LL22NC03-N14H11.1, and URHC, are upregulated in HCC and known to promote tumorigenesis in the liver by activating the MAPK/ERK signaling [ 66 , 67 , 68 ]. On the contrary, lncRNAs RUNX1-IT1 and CASC2 inactivate the MAPK/ERK signaling pathway and their expression is significantly downregulated in HCC [ 69 , 70 ].…”
Section: Mapk/erk Signaling Pathway In Hccmentioning
confidence: 99%